Genotype X environment interaction for grain yield of some lentil genotypes and relationship among univariate stability statistics - Dehghani, H.=700 1 Sabaghpour, S.H.; Sabaghnia, N.
(Es, En)
Ilus., 34 ref.
Keywords: LENS CULINARIS; INTERACCION GENOTIPO AMBIENTE; PRODUCCION; GRANOS; GENOTIPOS; ADAPTACION; METODOS ESTADISTICOS; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH